Anti-crisis management in educational institutions is the requirement of time - Cychuk Оlga (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського)
Anti-crisis management is aimed at qualitative changes and overcoming the crisis in the management of educational institutions, since the educational sector of Ukraine, like all spheres of society, has undergone serious changes in recent years. Heads of educational institutions faced the following tasks: organizing a safe educational environment, regulating personnel issues, providing psychological support to participants in the educational process, creating conditions for training IDPs, etc. The purpose of the study is to determine the features of anti-crisis management and analyze the results of the survey regarding the importance and necessity of training heads of educational institutions for anti-crisis management. The research used the following methods: analysis, generalization, systematization, questionnaire. It was found that anti-crisis management is a set of procedures, methods and techniques aimed at recognizing crises and creating conditions for their prevention, mitigating negative consequences and overcoming them for further effective functioning of the educational institution. Universal principles in any organization are: objectivity, comprehensiveness, responsibility, efficiency, control, legality. Depending on the field of activity, each organization, taking into account the main directions, will supplement and vary the specific principles of anti-crisis management. Anti-crisis management is a certain system and has its own mechanism, specific processes, technologies and management style. It was determined that the feature of anti-crisis management functions is that they should plan and implement measures that will lead to positive results before, during and after a crisis situation. Anti-crisis management methods are analyzed, including: diagnostic methods and methods aimed at overcoming crises (tactical, strategic). The process of anti-crisis management is specific, it involves working with crises that are difficult to predict in conditions of uncertainty, as they are caused by changes both at the national level and at the level of the organization’s external and internal environment.